2011
DOI: 10.1111/j.1540-8159.2010.02783.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonreentrant Supraventricular Tachycardia Misdiagnosed as Inappropriate Sinus Tachycardia

Abstract: We report a case of a woman with incessant palpitations initially misdiagnosed as inappropriate sinus tachycardia that proved refractory to β-blockers. At the time of electrophysiologic testing, a sustained narrow-complex tachycardia with a 1:2 atrioventricular relationship was repeatedly initiated by a posterior fascicle depolarization induced by means of a timed ventricular extrastimulus. The tachycardia was repeatedly terminated with a timed atrial extrastimulus, which excluded junctional bigeminy and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…One citation was suggested by a reviewer during the manuscript review process. Thus, 48 nonduplicate citations were eligible for inclusion 5–52 . Two articles described the same case so only the English language article was used 9,49 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One citation was suggested by a reviewer during the manuscript review process. Thus, 48 nonduplicate citations were eligible for inclusion 5–52 . Two articles described the same case so only the English language article was used 9,49 .…”
Section: Resultsmentioning
confidence: 99%
“…Atropine and isoproterenol, which suppress DAVNNT, are expected to exacerbate triggered junctional activity and have been suggested as a means to differentiate the two 10 . In the electrophysiology laboratory, termination of the tachycardia with a timed atrial extrastimuli that does not capture the His bundle has been suggested as a method to exclude junctional bigeminy 46 . Nevertheless, none of these features have been systematically evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The authors have previously described a patient with DAVNNT who was misdiagnosed as having inappropriate sinus tachycardia. [3] The differential diagnosis for a narrow complex tachycardia with a P:R ratio of 1:2 includes (1) atrial bigeminy with a low voltage P-wave masked by the preceding T-wave, (2) junctional bigeminy, and (3) atrioventricular nodal re-entrant tachycardia (AVNRT) with 2:1 retrograde block. [4] During electrophysiologic testing, the differential diagnosis includes junctional extrasytole and junction parasystole.…”
Section: Discussionmentioning
confidence: 99%
“…[2] The authors have demonstrated that atrial extrastimuli which terminate tachycardia without His capture effectively rule out junctional bigeminy. [3] Ultimately, definitive proof of DAVNNT is disappearance of the electrophysiologic manifestations of 1:2 AV conduction following slow pathway ablation. [2]…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of double firing or nonreentrant AV nodal tachycardia have been reported, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] including a case of tachycardia-induced cardiomyopathy. 11 However, our case is unique due to its presentation as a wide complex tachycardia and variable QRS morphologies secondary to possible gap physiology.…”
Section: Discussionmentioning
confidence: 99%